1996
DOI: 10.1128/iai.64.9.3833-3844.1996
|View full text |Cite
|
Sign up to set email alerts
|

NYVAC-Pf7: a poxvirus-vectored, multiantigen, multistage vaccine candidate for Plasmodium falciparum malaria

Abstract: The highly attenuated NYVAC vaccinia virus strain has been utilized to develop a multiantigen, multistage vaccine candidate for malaria, a disease that remains a serious global health problem and for which no highly effective vaccine exists. Genes encoding seven Plasmodium falciparum antigens derived from the sporozoite (circumsporozoite protein and sporozoite surface protein 2), liver (liver stage antigen 1), blood (merozoite surface protein 1, serine repeat antigen, and apical membrane antigen 1), and sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(32 citation statements)
references
References 86 publications
0
32
0
Order By: Relevance
“…TRAP is currently being investigated for its ability to elicit protective immunity in a sporozoite vaccine (Gilbert et al, 1997;Schneider et al, 1998) and in a multicomponent malaria vaccine (Tine et al, 1996;Ockenhouse et al, 1998;Shi et al, 1999). Previous reports have demonstrated that antibodies and cytotoxic T cells directed against TRAP of different Plasmodium species can interfere with sporozoite infectivity of hepatocytes (Potocnjak et al, 1980;Rogers et al, 1992;Müller et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…TRAP is currently being investigated for its ability to elicit protective immunity in a sporozoite vaccine (Gilbert et al, 1997;Schneider et al, 1998) and in a multicomponent malaria vaccine (Tine et al, 1996;Ockenhouse et al, 1998;Shi et al, 1999). Previous reports have demonstrated that antibodies and cytotoxic T cells directed against TRAP of different Plasmodium species can interfere with sporozoite infectivity of hepatocytes (Potocnjak et al, 1980;Rogers et al, 1992;Müller et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A different MVA vector encoding CSP also failed to prime antibody responses in humans that could be boosted by a particulate CSP protein-in-adjuvant vaccine, as would be predicted from preclinical studies [93]. Similarly, a NYVAC vector encoding seven different antigens from P. falciparum showed antibody induction in rhesus macaques as well as the advantages of poxviral delivery in terms of insert capacity and genotypic stability [94], however only low level antibody induction was observed in a Phase I/IIa trial where three homologous immunizations were given to healthy adults [95]. Encouragingly, a Phase I clinical trial using an ALVAC vector recombinant for rabies glycoprotein G did show neutralizing serum antibody induction in a dose-dependent manner, although titres achieved were lower than those following immunization with the standard human diploid cell culture rabies vaccine [96].…”
Section: Antibody Induction By Prime-boost Regimes -Clinical Experiencesmentioning
confidence: 93%
“…Several viral [96][97][98][99][100], bacterial [101][102][103][104] and parasite [105][106][107] vectors have been used in anti-malarial vaccine candidates; currently, many clinical trials are exploring their advantages to increase their potential and accelerate their use in vaccines [11,108].…”
Section: Recombinant Viral Vectors Vaccinesmentioning
confidence: 99%